PENGEMBANGAN APLIKASI ANDROID ‘AYO CUCI TANGAN’ UNTUK MENGAJARKAN KEBERSIHAN ANGGOTA TUBUH PADA MUATAN PELAJARAN IPA DI SEKOLAH DASAR - Muyassaroh Muyassaroh; Reno Nurdiyanto; Laifa Rahmawati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study aims to (1) produce an android application 'let's wash your hands' to teach body hygiene in science lesson content in elementary schools (2) determine the value of product feasibility. This type of research is research and development. This study uses a 4d model. This model consists of four steps; (1) define, (2) design, (3) development, and (4) disseminate. Product validation is calculated based on the results of expert assessments. The results of this research and development are (1) an android application with the topic of 'washing hands' (2) the media developed has a good feasibility value. Based on these findings, it shows that the 'let's wash your hands' android application is feasible to use in learning.